2015
DOI: 10.1097/bsd.0000000000000307
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Cervical Spine Injuries

Abstract: Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…Identifying children at risk of CSI is challenging, since physical examination can be unreliable [8]. In addition, trauma mechanisms in children differ from those in adults and are often associated with unique injury patterns, due to the anatomy of the paediatric cervical spine (C-spine) [5,9,10]. When clearing the C-spine in children, radiographic imaging is often used, despite this being costly and exposing children to radiation and its associated risks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Identifying children at risk of CSI is challenging, since physical examination can be unreliable [8]. In addition, trauma mechanisms in children differ from those in adults and are often associated with unique injury patterns, due to the anatomy of the paediatric cervical spine (C-spine) [5,9,10]. When clearing the C-spine in children, radiographic imaging is often used, despite this being costly and exposing children to radiation and its associated risks.…”
Section: Introductionmentioning
confidence: 99%
“…If CSI is suspected, various international trauma guidelines recommend plain radiography of the C-spine as primary imaging in children [11,16]. Its sensitivity for detecting CSI is higher than 90% [9,11,[17][18][19]. A CT scan of the C-spine is only indicated in those patients for whom a fracture is seen on plain radiography or for whom there is clinical suspicion of CSI despite a negative result with plain radiography [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Mortality was 33% in those with an upper cervical spine injury, versus 8.3% in lower cervical spine injury [1]. As with adults, males show a greater propensity to suffering cervical spine injury than females, at a ratio of 1.5–2.1:1 [2].…”
Section: Epidemiologymentioning
confidence: 99%
“…It was identified that if the child did not exhibit any of the five NEXUS criteria, then they did not have a cervical spine fracture [21]. However, only 2.8% of children in this study were under 2 years old and this group are the most difficult to assess in the emergency department [2].…”
Section: Clearing the Cervical Spine And Principles Of Imagingmentioning
confidence: 99%
“…Atlanto-axial rotatory-subluxation (AARS) is the most common pediatric cervical spine injury, 1 7 and can be classified according to Fielding and Hawkins assessing the direction and extent of atlas rotation (Fig. 1 ).…”
mentioning
confidence: 99%